TikTok’s Content materials: Its relevance, usefulness and motivation for english language learning in higher education - Zuraina, Ali; Muhammad Kamarul Kabilan, Abdullah; Ishtiaq, Muhammad (Nova Science Publishers, Inc., 2024)
This study explores the complex relationships between motivation scores and TikTok usage for English language learning. The study intends to provide important insights by examining the statistically significant correlations between motivation scores and both the content and perceived usefulness of TikTok. It also looks at possible differences in motivation scores between different age groups and student English proficiency levels. Surveys were used in this study, which involved 182 tertiary-level education students who used TikTok to learn English, in order to answer its research questions. The results hold significant implications for maximizing the use of TikTok in language learning and improving motivation with customized material. These observations help to explain TikTok’s efficacy as a tool for motivation, taking into account both content and functionality and illuminating potential differences based on age and degrees of English proficiency. With every aspect considered, the study offers practical suggestions on how teachers and students might use TikTok to enhance language learning.